MSMEs in Jatirasa, Bekasi: Design and Implementation of SAK-EMKM Financial Reports Using Microsoft Excel - Sari Mujiani; Elan Kurniawan; Patriandari Soedarso; Rianto Irvan (PT FORMOSA CENDEKIA GLOBAL, 2022)
In the last two years, there has been an increase in the number of MSME actors during the Covid-19 pandemic. However, MSMEs' development is not accompanied by knowledge of financial statement preparation. MSMEs face a number of challenges, including: a) a lack of knowledge about the preparation of accountable financial statements; and b) a lack of soft skills training about the accounting system. The proposed community service activities are expected to solve problems, such as: a) providing soft skills in the form of knowledge about financial reporting; and b) providing training on the preparation of financial statements using a computerized accounting system. The goals of this activity are as follows: a) increasing awareness of accountability for every transaction carried out in its business operations; and b) being consistent and sustainable in preparing financial statements for future business continuity.